2016
DOI: 10.3775/jie.95.480
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Morphology of Silica-Alumina Composites on Their Activity for Hydrolytic Dehydrogenation of Ammonia Borane

Abstract: In this work, we investigate the influence of the morphology of silica-alumina composites on their activity for hydrolytic dehydrogenation of ammonia borane. Three type of composites, hollow spheres, fine particles, and spherical particles are prepared by sol-gel method. The hollow spheres were prepared by using polystyrene particles as templates. The morphology of composites were observed by transmission electron microscopy. The activity of each type of composite for hydrolytic dehydrogenation of ammonia bora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 42 publications
0
11
0
Order By: Relevance
“…In order to evaluate the effect of the morphology and the dispersion of active aluminum species in the hollow spheres, the relation between the ratios of four-coordinated aluminum species and the activity for hydrogen evolution amount from aqueous solutions in the presence of various silica-aluminum composite particles. The relation calculated from some of our previous studies [52,61,62] was shown in Figure 5. From this figure, the hollow spheres showed unexpected high activity as compared with the fine particles, although the ratio of four-coordinated aluminum species in the hollow spheres was not significantly higher than the ratio of the fine particles.…”
Section: Improvement Of Dispersion Of Active Species Of Hollow Silicamentioning
confidence: 95%
See 3 more Smart Citations
“…In order to evaluate the effect of the morphology and the dispersion of active aluminum species in the hollow spheres, the relation between the ratios of four-coordinated aluminum species and the activity for hydrogen evolution amount from aqueous solutions in the presence of various silica-aluminum composite particles. The relation calculated from some of our previous studies [52,61,62] was shown in Figure 5. From this figure, the hollow spheres showed unexpected high activity as compared with the fine particles, although the ratio of four-coordinated aluminum species in the hollow spheres was not significantly higher than the ratio of the fine particles.…”
Section: Improvement Of Dispersion Of Active Species Of Hollow Silicamentioning
confidence: 95%
“…The specific surface areas of the hollow spheres and the fine particles were found to be 393 and 295 m 2 g −1 , respectively, indicating that the specific surface areas do not significantly differ from each other, and the primary particles including the hollow spheres were slightly small compared with the particle size of the fine particles. On the other hand, both the hollow spheres and the fine particles consisted of a typical amorphous silica-alumina from the results of powder XRD measurements [51,52].…”
Section: Influence Of the Morphology On The Activity For Hydrolytic Dmentioning
confidence: 99%
See 2 more Smart Citations
“…Additionally, NH 3 BH 3 releases hydrogen via a hydrolysis reaction in the presence of suitable acids and catalysts at room temperature (Eq. (1)) [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27]: NH 3 BH 3 + 2H 2 O → NH 4 + + BO 2  + 3H 2 (1) It has been reported that solid acids such as H-type zeolites (H-BEA and H-MOR) show high activity for the hydrolytic dehydrogenation of NH 3 BH 3 [13]. We have reported that hollow silica-alumina composite spheres show higher activity compared with fine particles [14].…”
Section: Introductionmentioning
confidence: 99%